Peningkatan Kemampuan Bahasa Dalam Pembelajaran Iqro Melalui Permainan Kartu Hijaiyah Pada Anak 4-5 Tahun Di Ra Darul Hikmah Gunung Gerbang Bantur - Arika Arika; Nikmahtul Khoir Tri Yula (Institut Agama Islam Negeri Metro, 2023)
Getting to know the Qur'an from an early age can be started by learning to recognize hijaiyah letters as a basis for learning the Qur'an. Based on observations, most children still have difficulty reading hijaiyah letters. Thus, researchers created game techniques that support children's language skills through the media of letter cards. The aim of the study was to describe the language learning process (iqro') and the results of improving reading skills in iqro' learning through letter card games for children aged 4-5 years at RA Darul Hikmah Gunung Gebang Kec. Bantur Regency Poor. The study of research methods used classroom action research (Action Research). The stages of each cycle go through planning, action, observation, and reflection processes. The data findings that will be improved include the first cycle of recognizing and memorizing hijaiyah letters, and the second cycle mentioning hijaiyah letters randomly and examining and sorting different forms of hijaiyah letters as an evaluation process. The final results of the research in the first cycle reached 60%, then in the second cycle it reached 87%, meaning that the hijaiyah letter card game technique proved effective in improving children's hijaiyah reading ability. It can be concluded that hijaiyah letter media with game techniques can significantly improve reading ability results. So, the suggested implementation is expected to be a benchmark for researchers to develop creative and innovative letter card media to improve children's language skills.